Review: Therapetic Approach in the Management of Osteoarthritis - Gawai, Snehal H.; Dhoble, Nilakshi N.; Padole, Nitin; Dhapke, Pankaj; Baheti, Jagdish R. Baheti (Asian Journal of Pharmaceutical Research and Development, 2023)
Objectives: The goal in designing sustained or controlled delivery systems is to reduce the frequency of dosing or to increase the effectiveness of the drug by localization at the site of action, reducing the dose required, and providing uniform drug delivery. A sustained release system is a type of modified drug delivery system that can be used as an alternative to a conventional drug delivery system. Summary: Osteoarthritis is a generative disease of synovial joints characterized by focal loss of articular hyaline cartilage with the proliferation of new bones and remodelling of joint contour. Risk factors of osteoarthritis are age, female gender, joint alignment, hereditary gene defect, joint injury and obesity.There are various symptoms of osteoarthritis and It diagnose by blood test, joint fluid test and MRI. Osteoarthritis is treated by self-care, medications, therapies, and surgeries. A sustained-release dosage form is a dosage form that maintains the therapeutic blood or tissue levels of the drug by continuous release of medication. Formulation of granules by wet granulation and the granules are evaluated by the pre-compression and post-compression studies. Conclusion: Sustained release tablet optimize drug release for extended time period.It maximized effectiveness, reduced side-effects of drug and cures the disease.